Hydrophobic oil-absorbing sponge, preparation method thereof and application of hydrophobic oil-absorbing sponge in coring tool

By using polyphenol compounds and polyamine compounds to construct the micro-nano rough structure of the sponge surface under the action of an oxidant, and performing low surface energy treatment, the problems of long and high cost of hydrophobic modification of the sponge surface in the prior art are solved, and the problem of high cost of hydrophobic modification in the existing technology is achieved. Efficient, uniform and low-cost preparation of hydrophobic oil-absorbing sponges.

CN119431877APending Publication Date: 2025-02-14SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310984194.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, dopamine is used to perform hydrophobic modification of sponge surfaces, which are problems such as long time, high concentration of dopamine required, uneven modification, poor repeatability and high production costs.

Method used

Polyphenol compounds and polyamine compounds are used as main raw materials to construct a micro-nano rough structure on the surface of the sponge under the action of an oxidant, and a hydrophobic oil-absorbing sponge is obtained through low surface energy treatment.

Benefits of technology

It has achieved the preparation of hydrophobic oil-absorbing sponge with short time, low cost, uniform modification and good repeatability. The surface water contact angle can reach up to 160° and the oil absorption ratio can reach up to 120g/g. It is suitable for applications such as drilling and centering tools.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431877A_ABST
    Figure CN119431877A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophobic oil-absorbing sponge, a preparation method thereof and application of the hydrophobic oil-absorbing sponge in a coring tool. According to the method, polyphenol compounds and polyamine compounds serve as main raw materials, under the action of an oxidizing agent, micro-nano structures are constructed on the surface of the sponge, then low-surface-energy treatment is conducted on the micro-nano structures, the hydrophobic oil-absorbing sponge is obtained, the method is short in time consumption, and the micro-nano structures with different hydrophobic properties and different morphologies are constructed on the surface of the sponge in a controllable mode; the concentration of the required polyphenol compound is low, hydrophobic modification can be carried out on the sponge with a larger size, the modification repeatability is good, and the cost is low; the water contact angle of the surface of the hydrophobic oil absorption sponge reaches 160 degrees, the oil absorption capacity reaches 120 times of the mass of the hydrophobic oil absorption sponge, and the hydrophobic oil absorption sponge is large in size and can be applied to a bushing of a drilling coring sponge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of super-hydrophobic oil-absorbing functional materials, and in particular relates to a hydrophobic oil-absorbing sponge, a preparation method thereof and application in a coring tool. Background Art

[0002] Drilling coring with a coring tool containing a sponge liner requires a sponge material with a large oil absorption capacity, fast oil absorption speed, the ability to retain oil to the ground for analysis, and a size that matches the liner. Sponges have a macroporous structure, which is conducive to rapid oil absorption and storage. They are also cheap and easy to obtain, and have excellent mechanical properties. Therefore, they are often used as substrates for hydrophobic modification. Methods for hydrophobic modification of sponge surfaces include etching, dip coating or deposition, in-situ chemical reaction, template method, hydrothermal method, sol-gel method, etc. Among them, dip coating is a simple and effective method for loading hydrophobic molecules, polymers or nanoparticles on the surface of a sponge skeleton, such as loading polydopamine (PDA) and SiO2, TiO2, magnetic nanoparticles, graphene (GO) nanosheets, etc. on the sponge surface. Then, through further reaction, long-chain alkyl hydrophobic agents are combined on the surface of the sponge skeleton to obtain super hydrophobic oleophilic sponge materials. Dopamine (DA) oxidizes and self-polymerizes under alkaline conditions to form polydopamine (PDA), which has strong surface adhesion and is a simple, green and environmentally friendly method for constructing superhydrophobic materials. However, this method has many disadvantages, such as: 1) It takes a long time, usually requiring the sponge to be soaked for 12 to 24 hours; 2) Only when the DA concentration is very high or particles are added separately can micro-nano structures be formed on the sponge surface; 3) The reaction of DA is easily affected by O2 in the air. When preparing large-sized sponge samples, the amount of DA solution required for the dip coating method is large, and the O2 content of different DA solution depths is different, which will lead to problems such as uneven sponge modification and poor repeatability of modification effects; 4) DA is expensive and has high production costs, which cannot meet the requirements of production activities such as drilling for hydrophobic and oleophilic sponge materials. Summary of the invention

[0003] One of the present invention provides a method for preparing a hydrophobic oil-absorbing sponge, which comprises the following steps:

[0004] 1) mixing a polyphenol compound and a first solvent to obtain a polyphenol compound solution;

[0005] 2) mixing the polyamine compound and the second solvent to obtain a polyamine compound solution;

[0006] 3) mixing the oxidant and the third solvent to obtain an oxidant solution;

[0007] 4) mixing the polyphenol compound solution, the polyamine compound solution and the oxidant solution to obtain a reaction solution;

[0008] 5) soaking the sponge in the reaction solution, taking it out, and placing it to obtain a modified sponge;

[0009] 6) mixing the low surface energy compound and the fourth solvent to obtain a low surface energy compound solution;

[0010] 7) soaking the modified sponge in a low surface energy compound solution, taking it out, and drying it to obtain the hydrophobic oil-absorbing sponge.

[0011] In one specific embodiment, the molar ratio of the polyamine compound to the polyphenol compound is (1 to 4):1;

[0012] and / or

[0013] The molar ratio of the oxidant to the polyphenol compound is 1:(1 to 4).

[0014] In a specific embodiment, the concentration of the polyphenolic compound in the polyphenolic compound solution, the concentration of the oxidant in the oxidant solution and the concentration of the low surface energy compound in the low surface energy compound solution are independently 2 mg / mL to 12 mg / mL; and / or

[0015] The concentration of the polyamine compound in the polyamine compound solution is 1 mg / mL to 6 mg / mL.

[0016] In one embodiment, the volume of the reaction solution is sufficient to completely immerse the sponge; and / or

[0017] The volume of the low surface energy compound solution is sufficient to completely immerse the modified sponge;

[0018] Preferably, the volume of the reaction solution is 1.2 to 1.5 times the volume of the sponge; and / or

[0019] The volume of the low surface energy compound solution is 1.2 to 1.5 times the volume of the modified sponge.

[0020] In a specific embodiment, the polyphenol compound is at least one of tannic acid, catechol and baicalein; and / or

[0021] The polyamine compound is polyvinyl polyamine and / or polyethylene imine; and / or

[0022] The oxidant is at least one of a peroxide, a mixture of a peroxide and a transition metal salt, a periodate and a persulfate; and / or

[0023] The low surface energy compound is a long-chain alkylamine and / or a long-chain alkylthiol.

[0024] In one embodiment, the polyvinyl polyamine is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine; and / or

[0025] The weight average molecular weight of the polyethyleneimine is 400 to 800; and / or

[0026] The long-chain alkylamine is C 12 To C 18 long chain alkylamines; and / or

[0027] The long-chain alkyl mercaptan is C 12 To C 18 long chain alkyl mercaptan; and / or

[0028] Preferably, the peroxide is hydrogen peroxide; and / or

[0029] The transition metal salt is selected from at least one of copper sulfate, copper sulfate hydrate (e.g., CuSO4.5H2O), ferric chloride and ferric chloride hydrate (e.g., FeCl3.6H2O); and / or

[0030] In the mixture of peroxide and transition metal salt, the molar ratio of transition metal salt to peroxide is 1:(1 to 2); and / or

[0031] The periodate is sodium periodate and / or potassium periodate; and / or

[0032] The persulfate is at least one of ammonium persulfate, sodium persulfate and potassium persulfate.

[0033] In one embodiment, the first solvent, the second solvent and the third solvent are independently selected from at least one of water, a lower alcohol and a buffer solution with a pH value of 8 to 9; and / or

[0034] The fourth solvent is a lower alcohol;

[0035] Preferably, when the first solvent, the second solvent and the third solvent are independently selected from water and / or lower alcohols, a pH adjuster is independently added to the polyphenol compound solution in step 1), the polyamine compound solution in step 2) and the oxidant solution in step 3) to adjust the pH value to 8 to 9;

[0036] Preferably, the pH adjuster is a base;

[0037] Preferably, the buffer solution is a Tris buffer solution and / or a phosphate buffer solution;

[0038] Preferably, the buffer solution is a Tris buffer solution with a pH of 8.5 and a concentration of 10 mmol / L;

[0039] Preferably, the base is at least one of sodium hydroxide, potassium hydroxide and ammonia water;

[0040] Preferably, the concentration of the aqueous ammonia is 28wt% to 30wt%;

[0041] Preferably, the lower alcohol is at least one of methanol, ethanol and isopropanol;

[0042] Preferably, in step 3), when the oxidant in the oxidant solution is periodate, the third solvent is water and / or Tris buffer solution.

[0043] In one embodiment, in step 5), the sponge is soaked for 1 to 5 minutes; and / or is placed in the air for 0.5 to 2 hours; and / or

[0044] In step 7), the modified sponge is soaked for 2 hours to 6 hours; and / or the drying temperature is 25° C. to 50° C.

[0045] In a specific embodiment, the sponge is a melamine sponge and / or a polyurethane sponge.

[0046] The second aspect of the present invention provides a hydrophobic oil-absorbing sponge prepared by the method described in the first aspect of the present invention.

[0047] The hydrophobic oil-absorbing sponge prepared by the method of the first invention or the hydrophobic oil-absorbing sponge of the second invention is used in a drilling coring tool, especially in a sponge liner of a drilling coring tool.

[0048] Beneficial effects of the present invention:

[0049] In view of the problems that the prior art adopts the dip coating method to hydrophobically modify the surface of the substrate with dopamine as the main raw material, and the method for preparing hydrophobic and lipophilic materials is time-consuming, requires a high dopamine concentration, is not easy to construct a micro-nano rough structure on the substrate surface, requires a large amount of dopamine solution for hydrophobic modification of a large-sized substrate, and has uneven hydrophobic modification, poor repeatability of the modification effect, and high production cost, the present invention provides a hydrophobic oil-absorbing sponge, a preparation method thereof, and its application in a coring tool. The method for preparing a hydrophobic oil-absorbing sponge provided by the present invention uses polyphenol compounds and polyamine compounds as main raw materials, constructs a micro-nano rough structure on the sponge surface under the action of an oxidant, and then performs a low surface energy treatment on it to obtain a hydrophobic oil-absorbing sponge. The method is time-saving. It only requires soaking the sponge in a mixed solution of a polyphenol compound solution, a polyamine compound solution and an oxidant solution for 1 to 5 minutes, and then standing in the air for 0.5 to 2 hours to react. Different morphologies with different hydrophobic properties, such as spherical particles, strips, needles and ice flowers, can be controllably constructed on the sponge surface. The concentration of the polyphenol compound in the polyphenol compound solution used is low, only 2 to 12 mg / mL. The melamine sponge or polyurethane sponge with a size of 910 mm×400 mm×10 mm and 1000 mm×600 mm×10 mm can be hydrophobically modified, and the modification has good repeatability. The wide range of modifiable sponge sizes and stable modification effects can meet the needs of application scenarios including but not limited to sponge liners for drilling coring tools; the polyphenol compounds, polyamine compounds and oxidants used are cheap and easy to obtain, and the expensive dopamine commonly used in the prior art is not used, which greatly reduces the production cost; the hydrophobic oil-absorbing sponge prepared by the method provided by the present invention has a surface contact angle with water of up to 160°, an oil absorption rate of up to 120g / g, excellent hydrophobic oil absorption capacity, and can be reused. The oil absorption rate can still reach 118g / g after 20 times of repetition, and the oil absorption rate retention rate can reach 98%, which is suitable for promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a scanning electron microscope image of the strip-shaped micro-nanostructure on the surface of the modified sponge obtained in step 5) of Example 1;

[0051] Figure 2 is a scanning electron microscope image of the needle-like micro-nanostructure on the surface of the modified sponge obtained in step 5) of Example 2;

[0052] Figure 3 This is a scanning electron microscope image of the ice flower-like micro-nanostructure on the surface of the modified sponge obtained in step 5) of Example 4;

[0053] Figure 4 This is a scanning electron microscope image of the spherical particle micro-nano structure on the surface of the modified sponge obtained in step 5) of Example 5. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0055] The melamine sponges used in Examples 1, 3, 5 to 9 and the polyurethane sponges used in Examples 2 and 4 were purchased from Beijing Liqing Lanbo Plastic Products Co., Ltd.

[0056] Example 1

[0057] 1) dissolving tannic acid in methanol, adding a Tris buffer solution with a pH of 8.5 and a concentration of 10 mmol / L to obtain a tannic acid solution with a concentration of 2 mg / mL, wherein the volume ratio of methanol to the Tris buffer solution is 1:9;

[0058] 2) dissolving polyethyleneimine (weight average molecular weight of 400) in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a polyethyleneimine solution having a concentration of 1 mg / mL;

[0059] 3) dissolving sodium periodate in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a sodium periodate solution having a concentration of 2 mg / mL;

[0060] 4) sequentially adding the polyethyleneimine solution and the sodium periodate solution to the tannic acid solution to obtain a reaction solution, wherein the molar ratio of the polyethyleneimine to the tannic acid is 1:1, and the molar ratio of the sodium periodate to the tannic acid is 1:1;

[0061] 5) Soak a melamine sponge with a size of 910 mm×400 mm×10 mm in 4732 mL of the reaction solution for 1 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with strip-like micro-nano structures on the surface;

[0062] 6) dissolving octadecylamine in methanol to obtain an octadecylamine solution with a concentration of 12 mg / mL;

[0063] 7) Soak the modified sponge in 4732 mL of octadecylamine solution for 6 h, take it out, and dry it in a forced air oven at 50° C. to obtain a hydrophobic oil-absorbing sponge.

[0064] Example 2

[0065] 1) dissolving tannic acid in methanol, adding dropwise 30 wt % ammonia water to adjust the pH to 8.5, to obtain a tannic acid solution with a concentration of 12 mg / mL;

[0066] 2) dissolving ethylenediamine in methanol, adding dropwise 30 wt % ammonia water to adjust the pH to 8.5, to obtain a 6 mg / mL ethylenediamine solution;

[0067] 3) a mixture of FeCl3·6H2O and H2O2 in a molar ratio of 1:2 was dissolved in methanol, and 30 wt% ammonia water was added dropwise to adjust the pH to 8.5 to obtain an oxidant solution with a concentration of 12 mg / mL;

[0068] 4) sequentially adding the ethylenediamine solution and the oxidant solution to the tannic acid solution to obtain a reaction solution, wherein the molar ratio of ethylenediamine to tannic acid is 4:1, and the molar ratio of the oxidant (specifically FeCl3·6H2O and H2O2 in a molar ratio of 1:2) to tannic acid is 1:1;

[0069] 5) Soak a polyurethane sponge with a size of 910 mm×400 mm×10 mm in 4732 mL of the reaction solution for 3 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with a needle-like micro-nano structure on the surface;

[0070] 6) dissolving octadecyl mercaptan in methanol to obtain an octadecyl mercaptan solution with a concentration of 8 mg / mL;

[0071] 7) Soak the modified sponge in 4732 mL of octadecyl mercaptan solution for 6 h, take it out, and dry it in a forced air oven at 50° C. to obtain a hydrophobic oil-absorbing sponge.

[0072] Example 3

[0073] 1) dissolving tannic acid in ethanol, adding a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a tannic acid solution having a concentration of 8 mg / mL, wherein the volume ratio of ethanol to the Tris buffer solution is 1:3;

[0074] 2) dissolving tetraethylenepentamine in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a tetraethylenepentamine solution having a concentration of 4 mg / mL;

[0075] 3) dissolving ammonium persulfate in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain an ammonium persulfate solution having a concentration of 8 mg / mL;

[0076] 4) sequentially adding a tetraethylenepentamine solution and an ammonium persulfate solution to a tannic acid solution to obtain a reaction solution, wherein the molar ratio of tetraethylenepentamine to tannic acid is 2:1, and the molar ratio of ammonium persulfate to tannic acid is 1:3;

[0077] 5) Soak a melamine sponge with a size of 910 mm×400 mm×10 mm in 4368 mL of the reaction solution for 5 min, take it out, and place it in the air at room temperature (25° C.) for 0.5 h to obtain a modified sponge with a needle-like micro-nano structure on the surface;

[0078] 6) dissolving octadecyl mercaptan in ethanol to obtain an octadecyl mercaptan solution with a concentration of 10 mg / mL;

[0079] 7) Soak the modified sponge in 4368 mL of octadecyl mercaptan solution for 4 h, take it out, and dry it at 25° C. to obtain a hydrophobic oil-absorbing sponge.

[0080] Example 4

[0081] 1) dissolving tannic acid in isopropanol, and adding 28 wt % ammonia water to adjust the pH to 8.5 to obtain a 2 mg / mL tannic acid solution, wherein the volume ratio of isopropanol to ammonia water is 1:3;

[0082] 2) dissolving triethylenetetramine in water, adding 28 wt % ammonia water dropwise to adjust the pH to 8.5, to obtain a triethylenetetramine solution with a concentration of 2 mg / mL;

[0083] 3) dissolving a mixture of CuSO4·5H2O and H2O2 in a molar ratio of 1:1 in water, and adding 28 wt% ammonia water dropwise to adjust the pH to 8.5 to obtain an oxidant solution with a concentration of 2 mg / mL;

[0084] 4) sequentially adding the triethylenetetramine solution and the oxidant solution to the tannic acid solution to obtain a reaction solution, wherein the molar ratio of triethylenetetramine to tannic acid is 1:1, and the molar ratio of the oxidant (specifically, CuSO4·5H2O and H2O2 in a molar ratio of 1:1) to tannic acid is 1:4;

[0085] 5) Soak a polyurethane sponge with a size of 910 mm×400 mm×10 mm in 4368 mL of the reaction solution for 3 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with an ice flower-like micro-nano structure on the surface;

[0086] 6) dissolving dodecyl mercaptan in ethanol to obtain a dodecyl mercaptan solution with a concentration of 2 mg / mL;

[0087] 7) Soak the modified sponge in 4368 mL of dodecyl mercaptan solution for 6 h, take it out, and dry it at 25° C. to obtain a hydrophobic oil-absorbing sponge.

[0088] Example 5

[0089] 1) dissolving catechol in ethanol, adding a Tris buffer solution with a pH of 8.5 and a concentration of 10 mmol / L to obtain a catechol solution with a concentration of 10 mg / mL, wherein the volume ratio of ethanol to the Tris buffer solution is 1:1;

[0090] 2) dissolving diethylenetriamine in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a diethylenetriamine solution having a concentration of 5 mg / mL;

[0091] 3) dissolving sodium periodate in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a sodium periodate solution having a concentration of 10 mg / mL;

[0092] 4) sequentially adding a diethylenetriamine solution and a sodium periodate solution to a catechol solution to obtain a reaction solution, wherein the molar ratio of diethylenetriamine to catechol is 4:1, and the molar ratio of sodium periodate to catechol is 1:1;

[0093] 5) Soak a melamine sponge with a size of 910 mm×400 mm×10 mm in 4732 mL of the reaction solution for 3 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with a spherical particle micro-nano structure on the surface;

[0094] 6) dissolving octadecylamine in ethanol to obtain an octadecylamine solution with a concentration of 10 mg / mL;

[0095] 7) Soak the modified sponge in 4732 mL of octadecylamine solution for 2 h, take it out, and dry it at 25° C. to obtain a hydrophobic oil-absorbing sponge.

[0096] Example 6

[0097] 1) dissolving catechol in ethanol, adding a Tris buffer solution with a pH of 8.5 and a concentration of 10 mmol / L to obtain a catechol solution with a concentration of 8 mg / mL, wherein the volume ratio of ethanol to the Tris buffer solution is 1:1;

[0098] 2) dissolving tetraethylenepentamine in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a tetraethylenepentamine solution having a concentration of 4 mg / mL;

[0099] 3) dissolving sodium periodate in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a sodium periodate solution having a concentration of 6 mg / mL;

[0100] 4) sequentially adding a tetraethylenepentamine solution and a sodium periodate solution to a catechol solution to obtain a reaction solution, wherein the molar ratio of tetraethylenepentamine to catechol is 3:1, and the molar ratio of sodium periodate to catechol is 1:1;

[0101] 5) Soak a melamine sponge with a size of 910 mm×400 mm×10 mm in 5460 mL of the reaction solution for 3 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with a spherical particle micro-nano structure on the surface;

[0102] 6) dissolving octadecylamine in ethanol to obtain an octadecylamine solution with a concentration of 12 mg / mL;

[0103] 7) Soak the modified sponge in 5460 mL of octadecylamine solution for 2 h, take it out, and dry it at 25° C. to obtain a hydrophobic oil-absorbing sponge.

[0104] Example 7

[0105] 1) dissolving baicalein in ethanol, adding a Tris buffer solution with a pH of 8.5 and a concentration of 10 mmol / L to obtain a baicalein solution with a concentration of 6 mg / mL, wherein the volume ratio of ethanol to the Tris buffer solution is 3:2;

[0106] 2) dissolving tetraethylenepentamine in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a tetraethylenepentamine solution having a concentration of 6 mg / mL;

[0107] 3) dissolving sodium periodate in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a sodium periodate solution having a concentration of 6 mg / mL;

[0108] 4) sequentially adding a tetraethylenepentamine solution and a sodium periodate solution to the baicalein solution to obtain a reaction solution, wherein the molar ratio of tetraethylenepentamine to baicalein is 4:1, and the molar ratio of sodium periodate to baicalein is 1:1;

[0109] 5) Soak a melamine sponge with a size of 910 mm×400 mm×10 mm in 5460 mL of the reaction solution for 3 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with a spherical particle micro-nano structure on the surface;

[0110] 6) dissolving octadecylamine in ethanol to obtain an octadecylamine solution with a concentration of 8 mg / mL;

[0111] 7) Soak the modified sponge in 5460 mL of octadecylamine solution for 4 h, take it out, and dry it at 25° C. to obtain a hydrophobic oil-absorbing sponge.

[0112] Example 8

[0113] 1) dissolving catechol in ethanol, adding a Tris buffer solution with a pH of 8.5 and a concentration of 10 mmol / L to obtain a catechol solution with a concentration of 4 mg / mL, wherein the volume ratio of ethanol to the Tris buffer solution is 1:3;

[0114] 2) dissolving tetraethylenepentamine in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a tetraethylenepentamine solution having a concentration of 4 mg / mL;

[0115] 3) dissolving sodium periodate in a Tris buffer solution having a pH of 8.5 and a concentration of 10 mmol / L to obtain a sodium periodate solution having a concentration of 4 mg / mL;

[0116] 4) sequentially adding a tetraethylenepentamine solution and a sodium periodate solution to a catechol solution to obtain a reaction solution, wherein the molar ratio of tetraethylenepentamine to catechol is 4:1, and the molar ratio of sodium periodate to catechol is 1:1;

[0117] 5) Soak a melamine sponge with a size of 910 mm×400 mm×10 mm in 5460 mL of the reaction solution for 1 min, take it out, and place it in the air at room temperature (25° C.) for 2 h to obtain a modified sponge with a spherical particle micro-nano structure on the surface;

[0118] 6) dissolving octadecylamine in ethanol to obtain an octadecylamine solution with a concentration of 6 mgl / mL;

[0119] 7) Soak the modified sponge in 5460 mL of octadecylamine solution for 2 h, take it out, and air-dry it at room temperature (25° C.) to obtain a hydrophobic oil-absorbing sponge.

[0120] Example 9

[0121] Preparation of 1000mm×600mm×10mm hydrophobic oil-absorbing sponge:

[0122] A hydrophobic oil-absorbing sponge was prepared in the same manner as in Example 8, except that the size of the melamine sponge in step 5) of Example 8 was changed to 1000 mm×600 mm×10 mm.

[0123] Practical application of hydrophobic oil-absorbing sponge:

[0124] The hydrophobic oil-absorbing sponge with a size of 1000 mm × 600 mm × 10 mm prepared in this embodiment was assembled into the liner of a drilling coring tool to carry out drilling coring. After coring was completed, the liner of the coring tool was disassembled to observe that the structure of the hydrophobic oil-absorbing sponge was intact. The hydrophobic oil-absorbing sponge assembled in the liner was then taken out and dripped clean (meaning that no oil droplets would drip out of the hydrophobic oil-absorbing sponge when no external force was applied). The mass of the hydrophobic oil-absorbing sponge after oil absorption during the coring process was weighed and recorded. Combined with the initial mass of the hydrophobic oil-absorbing sponge prepared in this embodiment, the oil absorption ratio of the hydrophobic oil-absorbing sponge was calculated according to formula (1). The oil absorption ratio was determined to be 63 g / g after three measurements and the average value was calculated.

[0125] Experimental evaluation

[0126] 1. Evaluation of hydrophobic properties of hydrophobic oil-absorbing sponge

[0127] Take 5 different parts on the surface of the hydrophobic oil-absorbing sponge prepared in any one of Examples 1 to 8, drop 4 μL of water on each part, and measure the water contact angle (CA) of the surface of the hydrophobic oil-absorbing sponge using a video optical contact angle meter (Centra 20 Tensiometer), and calculate the average value as the surface water contact angle of the hydrophobic oil-absorbing sponge prepared in this example;

[0128] According to the above method, the water contact angles on the surfaces of the hydrophobic oil-absorbing sponges prepared in Examples 1 to 8 were measured respectively. The specific data are shown in Table 1.

[0129] Table 1. Water contact angles on hydrophobic oil-absorbing sponge surfaces

[0130]

[0131]

[0132] From the data in Table 1, it can be seen that the surface contact angles of the hydrophobic oil-absorbing sponges prepared in Examples 1 to 8 are in the range of 145° to 160°, and the hydrophobicity is good. Among them, the hydrophobic oil-absorbing sponge prepared in Example 6 has the best hydrophobicity, and its surface water contact angle reaches a super-hydrophobic degree of 160°.

[0133] 2. Evaluation of oil absorption performance of hydrophobic oil-absorbing sponge

[0134] The oil absorption ratios of the hydrophobic oil absorbent sponges prepared in Examples 1 to 8 were measured to evaluate the oil absorption performance of the hydrophobic oil absorbent sponges.

[0135] The calculation formula of oil absorption rate is:

[0136] Qt=(m t -m0) / m0 (1)

[0137] In formula (1), Qt is the oil absorption rate, in g / g; m0 is the initial mass of the hydrophobic oil-absorbing sponge, in g; m t It is the mass of the hydrophobic oil-absorbing sponge after absorbing oil, in g.

[0138] ⅰ Determination of initial oil absorption rate of hydrophobic oil-absorbing sponge:

[0139] Weigh and record the initial mass of the hydrophobic oil-absorbing sponge prepared in any one of Examples 1 to 8, immerse it in waste pump oil for saturated absorption, take out the hydrophobic oil-absorbing sponge after oil absorption, drip it clean (meaning that no oil droplets will drip out of the hydrophobic oil-absorbing sponge when no external force is applied), weigh and record the mass of the hydrophobic oil-absorbing sponge after oil absorption, and calculate the oil absorption rate Qt (g / g) of the hydrophobic oil-absorbing sponge according to formula (1). The hydrophobic oil-absorbing sponge prepared in each example is measured 3 times, and the average value is calculated as the initial oil absorption rate of the hydrophobic oil-absorbing sponge prepared in each example;

[0140] ⅱ Determination of oil absorption ratio and oil absorption performance retention rate of hydrophobic oil-absorbing sponge after repeated oil absorption for 20 times:

[0141] The adsorbed oil in the hydrophobic oil-absorbing sponge obtained in step i after oil absorption is squeezed out by squeezing, then washed with ethanol, dried at 50° C., immersed in waste pump oil for adsorption saturation, taken out the hydrophobic oil-absorbing sponge after repeated oil absorption once, dripped clean, weighed and recorded the mass after repeated oil absorption once, and calculated the oil absorption ratio of repeated oil absorption once according to formula (1); the adsorbed oil in the hydrophobic oil-absorbing sponge after repeated oil absorption once is squeezed out by squeezing, washed with ethanol, dried at 50° C., and then repeated oil absorption test is carried out according to the same method as that of determining the repeated oil absorption ratio until repeated oil absorption is repeated 20 times, and the oil absorption ratio of each repeated oil absorption experiment is calculated according to formula (1), and the oil absorption ratio range of repeated oil absorption 20 times is statistically calculated;

[0142] The initial oil absorption ratio, the oil absorption ratio range after repeated oil absorption for 20 times, and the oil absorption performance retention ratio range after repeated oil absorption for 1 to 20 times relative to the initial oil absorption ratio of the hydrophobic oil-absorbing sponges prepared in Examples 1 to 8 are specifically shown in Table 2.

[0143] Table 2. Oil absorption performance of hydrophobic oil-absorbing sponges

[0144]

[0145] The data in Table 2 show that the initial oil absorption ratio of the hydrophobic oil-absorbing sponges prepared in Examples 1 to 8 is 50 to 120, the oil absorption ratio after repeated oil absorption for 20 times is in the range of 45 to 118, and the oil absorption performance retention rate is 88% to 98%. This indicates that the hydrophobic oil-absorbing sponges prepared in Examples 1 to 8 have good and stable oil absorption performance and can be reused.

[0146] 3. Modified sponge surface micro-nanostructure morphology

[0147] The surface morphology of the modified sponge obtained in step 5) of Examples 1 to 8 was observed using a scanning electron microscope. Figures 1 to 4 .

[0148] from Figures 1 to 4 It was found that the surface of the modified sponge has micro-nanostructures with different morphologies: Figure 1 It shows that the surface of the modified sponge obtained in step 5) of Example 1 is a strip-shaped micro-nano structure; Figure 2 It shows that the surface of the modified sponge obtained in step 5) of Example 2 is a needle-like micro-nano structure; Figure 3 It shows that the surface of the modified sponge obtained in step 5) of Example 4 is an ice flower-like micro-nano structure; Figure 4 It shows that the surface of the modified sponge obtained in step 5) of Example 5 is a spherical particle micro-nano structure.

[0149] The surface of the modified sponge obtained in step 5) of Example 3 was observed to have a needle-like micro-nano structure similar to that of Example 2; the surface of the modified sponge obtained in steps 5) of Examples 6 to 8 was observed to have a spherical particle micro-nano structure similar to that of Example 5. In addition, the surface of the hydrophobic oil-absorbing sponge prepared in Examples 1 to 8 still had micro-nano structures similar to those of the corresponding modified sponge surfaces.

[0150] Combined with the water contact angle and oil absorption performance of the hydrophobic oil-absorbing sponges prepared in Examples 1 to 8 measured in Experiments 1 and 2 and the morphology of the modified sponge surface micro-nano structure obtained in step 5) of preparing the hydrophobic oil-absorbing sponges in Examples 1 to 8 observed in Experiment 3, it can be seen that the hydrophobic properties and oil absorption properties of hydrophobic oil-absorbing sponges with surface micro-nano structures of different morphologies are different. In practical applications, hydrophobic oil-absorbing sponges with surface micro-nano structures of different morphologies can be prepared according to the method provided by the present invention based on the requirements for the hydrophobic properties and oil absorption properties of the hydrophobic oil-absorbing sponges.

[0151] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A method for preparing a hydrophobic oil-absorbing sponge, comprising the following steps: 1) mixing a polyphenol compound and a first solvent to obtain a polyphenol compound solution; 2) mixing the polyamine compound and the second solvent to obtain a polyamine compound solution; 3) mixing the oxidant and the third solvent to obtain an oxidant solution; 4) mixing the polyphenol compound solution, the polyamine compound solution and the oxidant solution to obtain a reaction solution; 5) soaking the sponge in the reaction solution, taking it out, and placing it to obtain a modified sponge; 6) mixing the low surface energy compound and the fourth solvent to obtain a low surface energy compound solution; 7) soaking the modified sponge in a low surface energy compound solution, taking it out, and drying it to obtain the hydrophobic oil-absorbing sponge.

2. The method according to claim 1, characterized in that The molar ratio of the polyamine compound to the polyphenol compound is (1 to 4):1; and / or The molar ratio of the oxidant to the polyphenol compound is 1:(1 to 4).

3. The method according to claim 1 or 2, characterized in that: The concentration of the polyphenolic compound in the polyphenolic compound solution, the concentration of the oxidant in the oxidant solution and the concentration of the low surface energy compound in the low surface energy compound solution are independently 2 mg / mL to 12 mg / mL; and / or The concentration of the polyamine compound in the polyamine compound solution is 1 mg / mL to 6 mg / mL.

4. The method according to any one of claims 1 to 3, characterized in that The polyphenol compound is at least one of tannic acid, catechol and baicalein; and / or The polyamine compound is polyvinyl polyamine and / or polyethylene imine; and / or The oxidant is at least one of a peroxide, a mixture of a peroxide and a transition metal salt, a periodate and a persulfate; and / or The low surface energy compound is a long-chain alkylamine and / or a long-chain alkylthiol.

5. The method according to claim 4, characterized in that The polyvinyl polyamine is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine; and / or The weight average molecular weight of the polyethyleneimine is 400 to 800; The long-chain alkylamine is C 12 To C 18 long chain alkylamines; and / or The long-chain alkyl mercaptan is C 12 To C 18 long chain alkyl mercaptan; and / or Preferably, the peroxide is hydrogen peroxide; and / or The transition metal salt is selected from at least one of copper sulfate, copper sulfate hydrate, ferric chloride and ferric chloride hydrate; and / or The periodate is sodium periodate and / or potassium periodate; and / or The persulfate is at least one of ammonium persulfate, sodium persulfate and potassium persulfate.

6. The method according to any one of claims 1 to 5, characterized in that The first solvent, the second solvent and the third solvent are independently selected from at least one of water, a lower alcohol and a buffer solution with a pH value of 8 to 9; and / or The fourth solvent is a lower alcohol; Preferably, when the first solvent, the second solvent and the third solvent are independently selected from water and / or lower alcohols, a pH adjuster is independently added to the polyphenol compound solution in step 1), the polyamine compound solution in step 2) and the oxidant solution in step 3) to adjust the pH value to 8 to 9; Preferably, the pH adjuster is a base; Preferably, the buffer solution is a Tris buffer solution and / or a phosphate buffer solution.

7. The method according to any one of claims 1 to 6, characterized in that In step 5), the sponge is soaked for 1 to 5 minutes; and / or is placed in the air for 0.5 to 2 hours; and / or In step 7), the modified sponge is soaked for 2 hours to 6 hours; and / or the drying temperature is 25° C. to 50° C.

8. The method according to any one of claims 1 to 7, characterized in that The sponge is melamine sponge and / or polyurethane sponge.

9. A hydrophobic oil-absorbing sponge prepared by the method according to any one of claims 1 to 8.

10. Use of the hydrophobic oil-absorbing sponge prepared according to the method of any one of claims 1 to 8 or the hydrophobic oil-absorbing sponge according to claim 9 in a drilling coring tool, especially in a sponge liner of a drilling coring tool.